Theory of light sail acceleration by intense lasers: an overview. (1st April 2014) - Macchi, Andrea
Abstract: A short overview of the theory of acceleration of thin foils driven by the radiation pressure of superintense lasers is presented. A simple criterion for radiation pressure dominance at intensities around $5 × 10^{20}\ W cm^{-2}$ is given, and the possibility for fast energy gain in the relativistic regime is discussed.